Implementasi Model Pembelajaran Inkuiri Terbimbing Untuk Meningkatkan Minat Belajar Peserta Didik Pokok Bahasan Hukum Newton Tentang Gerak Pada Kelas X SMK Negeri 6 Tidore Kepulauan - Muksin, Marwiya; Ali, Nursanti (KUANTUM: Jurnal Pembelajaran dan Sains Fisika, 2025)
This Classroom Action Research Aims To Increase Student’s Interest In Learning The Subject Of Newton’s Laws By Using A Guided Inquiry Learning Model. This Research Was Carried Out At SMK Negeri 6 Tikep. The Research Method Used Was Classroom Action Research (PTK) Using 2 Cycles, Sampel Taken Were 17 Students And Divided Into Three Groups, Data Collection In This Research Used Interview Transcripts And Questionnaires. The Result Of The Research Showed That The Average Value Of Learning Interest Using The Inquiry Model To Increase Students Interest In Learning At SMK Negeri 6 Tikep On The Consept Of Newton’s Law Of Motion In Cycle I Was 59.18 And In Cycle II There Was An Increase Of 73.71. The Research Result Show That (1) Learning Management Using Guided Inquiry With An Average Score Of 3.4 Is Quite Good. (2) There Is An Influence Of The Guided Inquiry Learning Model On Interest In Learning With A Significant Value Of 73.71. Which Means There Is An Increase In Interest In Learning By Using The Guided Inquiry Learning Model.